2010
DOI: 10.1177/039463201002300320
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcoholism Pharmacotherapy on Immune Responses in Alcohol-Dependent Patients

Abstract: Chronic alcohol use has profound modulatory effects on the immune system. Both the innate and the acquired immunity are compromised. The use of pharmacotherapy is increasingly applied to enhance the percentage of success in maintaining alcoholic patients in remission. Disulfiram, naltrexone and gamma hydroxybutiric acid are the drugs used for this purpose in Italian Addiction Services. In this study we analyze the effect of pharmacotherapy of alcohol dependence on immune responses in alcoholics. Six groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In one study, proinflammatory cytokine TNF-α levels, lymphoproliferation, and peripheral mononuclear cell production of the Th1 cytokine IFN-γ decreased as Th2 cytokine IL4 levels increased, which consequently altered the Th1/Th2 equilibrium. 26 Another study demonstrated that stimulated Kupffer cells induced oxidative stress and produced proinflammatory cytokines (eg, TNF-α), which resulted in hepatocellular damage. 16 However, these data support a mechanism that may rely on ethanol synergizing with LPS to upregulate the induction of TNF gene expression and TNF overproduction by decreasing cellular cAMP levels in monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, proinflammatory cytokine TNF-α levels, lymphoproliferation, and peripheral mononuclear cell production of the Th1 cytokine IFN-γ decreased as Th2 cytokine IL4 levels increased, which consequently altered the Th1/Th2 equilibrium. 26 Another study demonstrated that stimulated Kupffer cells induced oxidative stress and produced proinflammatory cytokines (eg, TNF-α), which resulted in hepatocellular damage. 16 However, these data support a mechanism that may rely on ethanol synergizing with LPS to upregulate the induction of TNF gene expression and TNF overproduction by decreasing cellular cAMP levels in monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In human opiate addicts, the level of TNF-α expression in the brain (locus coeruleus) is higher than that in control subjects (Dyuizen and Lamash 2009). Levels of circulating TNF-α are altered in alcoholics, opiate addicts, and cocaine or marijuana abusers (Baldwin et al 1997;Peng et al 1999;Irwin et al 2007Irwin et al , 2009Gonzalez-Quintela et al 2008;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010), and TNF-α may be a candidate biomarker of alcohol abuse and alcoholism (Achur et al 2010). In our study in animal, TNF-α (−/−) mice were more sensitive to METH self-administration and had a higher motivation for getting METH than wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Yet reports of the level of circulating TNF-α in human alcoholics, opiate addicts, and cocaine or marijuana abusers are not consistent. Some reports show that the level increases (Gonzalez-Quintela et al 2008;Peng et al 1999;Irwin et al 2009), and others show that the level decreases or does not change (Baldwin et al 1997;Irwin et al 2007;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010). In animals, repeated administration of psychostimulants or opiates induced TNF-α production in the brain or immune system (Friedman and Eisenstein 2004;Nakajima et al 2004;Niwa et al 2007a; Kubera et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study of 5 groups with alcohol dependence by Franchi et al 36 concluded that pharmacotherapy may ameliorate the immune system in alcoholic patients more than with group therapy (Table 6). …”
Section: Dsf and Immunologymentioning
confidence: 99%